Reasons for not receiving the HPV vaccine among eligible adults: Lack of knowledge and of provider recommendations contribute more than safety and insurance concerns - Joël Fokom Domgue; Sonia A. Cunningham; Robert K. Yu; Sanjay Shete (Cancer Medicine, 2020)
Abstract Background The upward trends of vaccine exemptions in Texas are alarming. While HPV vaccine rates in this State are among the lowest nationwide, factors that contribute to the low HPV vaccination uptake among adults remain unknown. In this study, we examined the main reasons for not receiving HPV vaccination among age‐eligible adults. Methods The Texas health screening survey (2018), a multistage area probability design‐based survey of a representative sample of Texas residents, was used to identify 907 eligible adults (age ≥ 18 years) respondents, including 724 women aged ≤ 26 years in 2007 (≤38 years in 2018), and 183 men aged ≤ 21 years in 2011 (≤28 years in 2018). Participants who reported having never received an HPV shot, where asked the main reason for not receiving the vaccine. Results Overall, 58.5% (95%CI: 55.1‐62.0) of vaccine eligible adults reported having never received the HPV vaccine. The most commonly reported reasons for not receiving it were: did not know about the vaccine (18.5% (14.9‐22.1)), and provider did not recommend (14.1% (10.9‐17.4)). In contrast, commonly perceived reasons such as: safety concerns (7.2% (4.8‐9.5)), lack of insurance (3.4% (1.7‐5.1), and concerns about increasing sexual activity if vaccinated (0.2% (0.0‐0.5)), were less frequently reported. Conclusion Among vaccine‐eligible adults, safety and sexuality concerns do not appear to be the prime factors underlying low HPV vaccination rates. Rather than emphasizing them, educational interventions should aim at improving vaccine's knowledge, and enhancing provider recommendations on the necessity of HPV vaccination.